2001
DOI: 10.1046/j.1365-2265.2001.01256.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased arterial intima‐media thickness by B‐M mode echodoppler ultrasonography in acromegaly

Abstract: A significant increase of IMT of both common carotid arteries was observed in patients with active acromegaly, this was also found in those cured from acromegaly. However, the prevalence of well defined carotid plaques was not increased in both groups of patients with acromegaly as compared to controls. On this basis, heart more than vessels seems to be affected by chronic GH and IGF-I excess in acromegaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
2
11

Year Published

2002
2002
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 59 publications
6
71
2
11
Order By: Relevance
“…Thus, there was no evidence for an increased CVD risk or premature CAD in patients with newly diagnosed and treatment-naive acromegaly. This is consistent with an earlier study that demonstrated that the prevalence of atherosclerotic plaques in the common and internal carotid arteries was not higher than in controls (37).…”
Section: Discussionsupporting
confidence: 82%
“…Thus, there was no evidence for an increased CVD risk or premature CAD in patients with newly diagnosed and treatment-naive acromegaly. This is consistent with an earlier study that demonstrated that the prevalence of atherosclerotic plaques in the common and internal carotid arteries was not higher than in controls (37).…”
Section: Discussionsupporting
confidence: 82%
“…In this respect, it is worth noting that while almost one-half of acromegalic patients of this series presented cardiac anomalies, only three of them had documented coronary artery disease. Moreover, previous studies reported that in acromegalic patients well-defined carotid wall plaques were as frequent as in healthy subjects (36), consistent with the view that atherosclerotic vascular damage does not represent the main determinant of elevated cardiovascular mortality in acromegaly (23).…”
Section: Discussionsupporting
confidence: 68%
“…These data suggest a beneficial effect of IGF-I on the vasculature. In contrast, the correction of growth hormone overproduction in acromegalic patients also resulted in reversion of IMT thickening (37). Therefore, the influence of the IGF-system on atherosclerosis is complex and may be substantially modulated by the metabolic state.…”
Section: Linear Regression Analysesmentioning
confidence: 89%